E-Modul Biologi Terintegrasi Keilmuan Islam Berbasis Android - A. Muh. Farid Khuzairi; Ainul Uyuni Taufiq; Hamansah (Al-AHYA: Jurnal Pendidikan Biologi, 2022)
This study aims to develop an android-based Islamic science integrated biology e-module, find out the level of validity of the e-module and find out the level of practicality of the android-based Islamic science integrated biology e-module in class X MAN 3 Makassar. This research includes research and development which refers to the 4-D development model, which includes four stages, namely preparation (define), design (design), development (develop), and dissemination (disseminate). The subjects of this study were 25 students of class X MIPA I, the instruments used were expert validation sheets, educator response questionnaires and student response questionnaires. Based on the results of the expert validator assessment, the level of validity of the android-based Islamic science integrated biology e-module is 3.30 (2.5 ≤ M ≤ 3.5), and is included in the valid category. The results of the assessment of the responses of educators and students showed a value of the practicality level of the e-module of 3.50 (Xi = 3.5), and belonged to the category of very practical.